2021
DOI: 10.1371/journal.pone.0252388
|View full text |Cite
|
Sign up to set email alerts
|

Lack of efficacy of hydroxychloroquine and azithromycin in patients hospitalized for COVID-19 pneumonia: A retrospective study

Abstract: Background Hydroxychloroquine combined with azithromycin (HCQ/AZI) has initially been used against coronavirus disease-2019 (COVID-19). In this retrospective study, we assessed the clinical effects of HCQ/AZI, with a 28-days follow-up. Methods In a registry-study which included patients hospitalized for COVID-19 between March 15 and April 2, 2020, we compared patients who received HCQ/AZI to those who did not, regarding a composite outcome of mortality and mechanical ventilation with a 28-days follow-up. QT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The findings from the large RECOVERY trial confirmed several previous studies that found modest or no benefit in azithromycin use in patients admitted to hospital with COVID-19 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The findings from the large RECOVERY trial confirmed several previous studies that found modest or no benefit in azithromycin use in patients admitted to hospital with COVID-19 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 81%
“…Two-hundred-forty-five studies were excluded for not reporting data on antibiotic use in COVID-19 patients. From the remaining 118 studies, 36 studies were included in this systematic review ( Figure 1 ) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the studies included in the two groups is provided in Data S1 12–194 . The literature search yielded a total of 826 citations.…”
Section: Data Extractionmentioning
confidence: 99%
“…On the other hand, azithromycin, which was frequently prescribed alongside hydroxychloroquine to treat COVID-19, had no significant effect on viral titers in Vero E6 cells. Hydroxychloroquine and azithromycin have now been shown to have negative side effects and low to no efficacy in COVID-19 patients [29,30]. These results highlight that numerous, potentially efficacious, drugs should be tested in clinical settings because in vivo outcomes are not always reflected in in vitro systems and vice versa.…”
Section: Screen Of Fda-approved Compounds Against Sars-cov-2mentioning
confidence: 99%